A multi-country study of harms to children because of others’ drinking - Laslett, Anne-Marie; Rankin, G.; Waleewong, O.; Callinan, S.; Hoang, H.; Florenzano, R.; Hettige, S.; Obot, I.; Siengsounthone, L.; Ibanga, A.; Hope, A.; Landberg, J.; et al. (Alcohol Research Documentation, Inc Rutgers, 2017)
Objective: This study aims to ascertain and compare the prevalence and correlates of alcohol-related harms to children crossnationally. Method: National and regional sample surveys of randomly selected households included 7,848 carers (4,223 women) from eight countries (Australia, Chile, Ireland, Lao People’s Democratic Republic [PDR], Nigeria, Sri Lanka, Thailand, and Vietnam). Country response rates ranged from 35% to 99%. Face-to-face or telephone surveys asking about harm from others’ drinking to children ages 0–17 years were conducted, including four specific harms: that because of others’ drinking in the past year children had been (a) physically hurt, (b) verbally abused, (c) exposed to domestic violence, or (d) left unsupervised. Results: The prevalence of alcohol-related harms to children varied from a low of 4% in Lao PDR to 14% in Vietnam. Alcohol-related harms to children were reported by a substantial minority of families in most countries, with only Lao PDR and Nigeria reporting significantly lower levels of harm. Alcohol-related harms to children were dispersed sociodemographically and were concentrated in families with heavy drinkers. Conclusions: Family-level drinking patterns were consistently identified as correlates of harm to children because of others’ drinking, whereas sociodemographic factors showed few obvious correlations. © 2017, Alcohol Research Documentation Inc. All rights reserved.